Cobalt-salen intercalated montmorillonite catalyst for air oxidation of p-cresol under mild conditions - Rode, Chandrashekhar V.; Kshirsagar, Vikas S.; Nadgeri, Jayprakash M.; Patil, Kashinath R. (Industrial & Engineering Chemistry Research, 2007)
Air oxidation of p-cresol under very mild conditions (338 K and ambient pressure) was carried out in a semibatch reactor over a solid catalyst developed by intercalating cobalt-salen into the montmorillonite clay. The intercalation of cobalt - salen was done by a simple protocol, and the characterization of the intercalated catalyst was done by XPS, FTIR, and XRD techniques. A total selectivity >= 90% to the oxidation products could be achieved with this solid catalyst by eliminating the undesired coupling side products in air oxidation of p-cresol under ambient pressure conditions. Effect of various process parameters on the conversion and selectivity pattern were also studied, and it was found that the selectivity ratio of aldehyde to alcohol could be varied by suitably changing the reaction conditions. This heterogeneous catalyst was found to give a 5-fold higher turnover number than the homogeneous cobalt - salen complex.
Joint 6th International Symposium on Catalysis in Multiphase Reactors/5th International Symposium on Multifunctional Reactors (CAMURE-6/ISMR-5-), Pune, INDIA, JAN 14-17, 2007

Confinement of nano CdS in designated glass: a novel functionality of quantum dot-glass nanosystems in solar hydrogen production - Kale, Bharat B.; Baeg, Jin-Ook; Apte, Sanjay K.; Sonawane, Ravindra S.; Naik, Sonali D.; Patil, Kashinath R. (Journal of Materials Chemistry, 2007)
The present work is the investigation of our novel approach to designing quantum dot-glass nanosystems by confining nano CdS in designated glass and the first employment of such a quantum dot system in solar hydrogen production. The CdS quantum dots were grown in a special glass matrix, which involved a sequence of steps. The obtained glass was of uniformly bright yellow in color and the bulk glass was pulverized to a fine powder of micron size particles. The glass powder was characterized structurally and morphologically. X-Ray diffraction and electron diffraction patterns reveal a hexagonal crystallite system for the CdS quantum dots. Field emission scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, X-ray fluorescence spectroscopy and chemical leaching with HCl studies demonstrate that the 2.5 nm size CdS quantum dots distribute homogeneously in a monodispersed form in the glass domain and on the surface with a ``partially embedded exposure'' configuration. This disposition imparts an excellent photostability against photocorrosion and also a facile catalytic function. Therefore, even a very small amount of CdS quantum dots (0.005 g per gram of glass powder) is able to photodecompose H2S under visible light (lambda >= 420 nm) both in alkaline and pure aqueous media and produce solar hydrogen with markedly high quantum yields of 17.5 and 11.4%, respectively at 470 nm. Salient features like reusability after simple washing, corrosionless-stability and remarkable catalytic activity of this quantum dot-glass nanosystem are brought forth by our novel catalyst design and are much acclaimed in large scale solar H-2 production.

Highly active nanostructured Co3O4 catalyst with tunable selectivity for liquid phase air oxidation of p-cresol - Kshirsagar, Vikas S.; Vijayanand, Subramanian; Potdar, Hari S.; Joy, Pattayil Alias; Patil, Kashinath R.; Rode, Chandrashekhar V. (Chemistry Letters, 2008)
This is a first report of highly efficient heterogeneous nanostructured Co3O4 catalyst (6-8 nm) having high surface area (95 m(2)/g) developed for selective liquid phase air oxidation of p-cresol under atmospheric pressure conditions.

Kinetics of PbCrO(4) nanorod growth by oriented attachment at the air-water interface - Hawaldar, Ranjit R.; Sathaye, Shivaram D.; Harle, Arti S.; Gholap, Ramkrishna S.; Patil, Kashinath R. (Journal of Physical Chemistry C, 2008)
Oriented attachment is a new way of crystal growth to transform preformed nanoparticles into hierarchical assemblies. Here, we demonstrate the use of liquid-liquid interfaces toward the formation of PbCrO(4) nanoparticles and their subsequent time-dependent self-assembly at the air-water interface into nanorods by oriented attachment. EDAX and XPS analysis indicate the formation of stoichiometric PbCrO(4). TEM studies at different stages of aging reveal that the transformation from nanoparticles to nanorods is kinetically governed. HRTEM analysis indicates nanorod growth along the [110] plane. UV-visible spectra reveal the presence of peaks at 425 and 515 nm for nanorods, while for the nanoparticle sample, a single peak at 425 urn is evident. As formation of ultrathin films over a large area (typically equal to or greater than 1 mu m x 1 mu m) concomitantly accompanies this approach, it can be extended to other materials as well for nanostructured device applications.

Heterogeneous cobalt-saponite catalyst for liquid phase air oxidation of p-cresol - Kshirsagar, Vikas S.; Garade, Ajit C.; Patil, Kashinath R.; Jha, Ratnesh Kumar; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2009)
Heterogeneous Co-saponite was found to be an efficient catalyst for the liquid phase oxidation of p-cresol under mild conditions. Divalent cobalt tons were found to be in both the tetrahedral and octahedral positions of the saponite clay. Studies on the effect of reaction parameters showed that the rate of reaction increased with increase in Co loading from 5 to 13% and then remained constant up to 30% of Co loading, while the rate of oxidation showed a first-order dependence on the partial pressure of oxygen up to 300 kPa. Results of oxidation experiments over Co-saponite, in an Inert atmosphere, and the XPS studies Suggest Mars-van Krevelen pathway operating, which involves lattice oxygen of Co-saponite in the liquid phase oxidation of p-cresol.

Liquid phase oxidation of p-cresol over cobalt saponite - Kshirsagar, Vikas S.; Garade, Ajit C.; Patil, Kashinath R.; Shirai, Masayuki; Rode, Chandrashekhar V. (Topics in Catalysis, 2009)
Liquid phase oxidation of p-cresol was carried out over a Co-saponite catalyst in a temperature and pressure range of 333-393 K and 20-827 kPa, respectively in n-propanol. Co-saponites with varying cobalt content (5-30%) were prepared and screened among which 13% Co-saponite gave the highest conversion of 92% of p-cresol with 92% selectivity to p-hydroxybenzaldehyde without formation of any non-oxidation products.
Keywords: Co-saponite; Liquid phase oxidation; p-Cresol; p-Hydroxybenzaldehyde; XPS

Ecofriendly synthesis and solar photocatalytic activity of S-doped ZnO - Patil, Ashokrao B.; Patil, Kashinath R.; Pardeshi, Satish K. (Journal of Hazardous Materials, 2010)
The S-doped ZnO was prepared by new ecofriendly method, which involves simple mechanochemical synthesis followed by thermal decomposition of bisthiourea zinc oxalate (BTZO) powders. The BTZO was characterized by FTIR and TG-DTA analysis while S-doped ZnO crystallite was characterized by XRD, XPS, SEM, EDXS, and photoluminescence (PL) spectra. X-ray diffraction data suggest the single phase wurtzite structure for S-doped ZnO and the incorporation of sulfur expand the lattice constants of ZnO. Room temperature PL spectra show more number of oxygen vacancies in S-doped ZnO as compare to that of pure ZnO. Photocatalytic activity of S-doped ZnO was checked by means of solar photocatalytic degradation (PCD) of resorcinol, using a batch photoreactor. The PCD efficiency of S-doped ZnO was found to be 2 times greater than that of pure ZnO. The inherent relationship between PL intensity and photocatalytic activity of S-doped ZnO was discussed. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Photocatalysis; photoluminescence; Resorcinol; S-doped ZnO; Sunlight; XPS

Fabrication, characterization and electrochemical performance of single strand carbon fiber prepared by catalytic chemical vapor decomposition method - Joshi, Vrushali S.; Gokhale, Suresh P.; Patil, Kashinath R.; Haram, Santosh K. (Electrochimica Acta, 2010)
Preparation, fabrication and voltammetric characterizations of a single strand of carbon fiber (SSCF) electrode and their potential applications for biosensor are presented. SSCFs of diameter ca. 10 +/- 2 mu m and few millimeters in length are prepared by catalytic chemical vapor decomposition (CCVD) method. Voltammetry with potassium ferricyanide. alpha-methylferrocene methanol and hexaammineruthenium(III) chloride on SSCF electrode are used as bench marks to validate the electrode properties. Quasi-steady state voltammograms obtained were fitted into a cylindrical diffusion model From which, the standard rate constant (k(0)) and electron transfer coefficient (alpha) are obtained. The use of SSCF electrode is demonstrated for the voltammetric detection of the micromolar quantity of dopamine in the presence of large excess (ca. 200 times) of ascorbic acid, without any fouling of electrode surface. The kinetics of electron transfer are investigated. (C) 2009 Elsevier Ltd All rights reserved.
Keywords: alpha-Methylferrocene methanol; Ascorbic acid; Catalytic chemical vapor decomposition (CCVD); Cylindrical diffusion; dopamine; Hexaammineruthenium(III) chloride; Single strand carbon fiber (SSCF) electrode

Thermal conductivity measurement of polyglycol alkyl ethers at temperatures from (303.15 to 393.15) K - Salavera, Daniel; Patil, Kashinath R.; Coronas, Alberto (Journal of Chemical and Engineering Data, 2010)
Experimental Values of the thermal conductivity of five pure polyglycol alkyl ethers are presented in a temperature range from (303.15 to 393.15) K at a pressure of 1 MPa. Measurements were made with a Setaram C-80 II calorimetric device equipped with a suitable vessel Setup and ail auxiliary thermostat to measure at high-temperature conditions using the steady-state coaxial cylinders method. The measured values of the thermal conductivity were compared with data reported in the literature. The reliability and accuracy of the experimental method were confirmed with the measurements on pure benzene with well-known thermal conductivity values. Our data agreed with the limited data available in the literature and were correlated using an empirical expression. The Uncertainty of the results was estimated to be within 2.0 %, and the reproducibility of the data was better than +/- 0.5 %.

Efficiency and recycling capability of montmorillonite supported Fe-Ni bimetallic nanocomposites towards hexavalent chromium remediation - Kadu, Brijesh S.; Sathe, Yogesh D.; Ingle, Abhijit B.; Chikate, Rajeev C.; Patil, Kashinath R.; Rode, Chandrashekhar V. (Applied Catalysis B-Environmental, 2011)
The remediation of Cr(VI) from simulated water streams is investigated using Fe-Ni bimetallic nanoparticles (Fe-Ni NPs) and their nanocomposites prepared with montmorillonite (MMT) clay. These nanocomposites are characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and Brunauer-Emmett-Teller (BET) surface area analyses. XRD analysis revealed proper dispersion as well as intercalation of Fe-Ni NPs in the clay matrix. TEM of nanocomposites showed the presence of spherical particles having a size of 20-40 nm. Batch experiments with a 25 mg L(-1) Cr(VI) solution and 2 g L-1 Fe-Ni NPs exhibited complete reduction of Cr(VI) within 10 min that follows first order reaction kinetics. Amongst 25%, 50%, 75% in situ and loaded nanocomposites, 75% compositions possess better activity with enhanced reduction capacity below pH 4 due to generation of reactive H center dot species. XPS analysis of nanocomposites after Cr(VI) treatment suggested that reduction process occurs through Cr(111) formation followed by its subsequent reduction to Cr(0). Their potentiality towards reusage is established from the recycling experiments that revealed the order of efficiency as 75% in situ > Fe-Ni NPs > 75% loaded nanocomposites. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Cr(VI) remediation; Iron-nickel bimetallics; Montmorillonite; Nanocomposites; Recycling

Enhancement of oxygen vacancies and solar photocatalytic activity of zinc oxide by incorporation of nonmetal - Patil, Ashokrao B.; Patil, Kashinath R.; Pardeshi, Satish K. (Journal of Solid State Chemistry, 2011)
B-doped ZnO and N-doped ZnO powders have been synthesized by mechanochemical method and characterized by TG-DTA, XRD, SEM-EDX, XPS, UV-visible and photoluminescence (PL) spectra. X-ray diffraction data suggests the hexagonal wurtzite structure for modified ZnO crystallites and the incorporation of nonmetal expands the lattice constants of ZnO. The room temperature PL spectra suggest more number of oxygen vacancies exist in nonmetal-doped ZnO than that of undoped zinc oxide. XPS analysis shows the substitution of some of the O atoms of ZnO by nonmetal atoms. Solar photocatalytic activity of B-doped ZnO, N-doped ZnO and undoped ZnO was compared by means of oxidative photocatalytic degradation (PCD) of Bisphenol A (BPA). B-doped ZnO showed better solar PCD efficiency as compare to N-doped ZnO and undoped ZnO. The PCD of BPA follows first order reaction kinetics. The detail mechanism of PCD of Bisphenol A was proposed with the identification of intermediates such as hydroquinone, benzene-1,2,4-triol and 4-(2-hydroxypropan-2-yl) phenol. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Bisphenol A; Enhanced oxygen vacancies; Nonmetal doping; Photocatalysis; Sunlight

Self assembled CdLa2S4 hexagon flowers, nanoprisms and nanowires: novel photocatalysts for solar hydrogen production - Kale, Bharat B.; Baeg, Jin-Ook; Kong, Ki-jeong; Moon, Sang-Jin; Nikam, Latesh K.; Patil, Kashinath R. (Journal of Materials Chemistry, 2011)
We report here a new ternary chalcogenide material, cadmium lanthanum sulfide (CdLa2S4) produced using a facile hydrothermal method at 433 K. The effect of the solvent on the morphology of the CdLa2S4 was demonstrated for the first time. The prima facie observations revealed the formation of highly crystalline hexagonal structures in the form of flowers in aqueous medium. The flowers comprise hexagonal columns similar to 300 nm in diameter and 1-1.2 mu m in length. All the hexagonal structures have a sharp tip with a cavity of 10 nm and are almost equal in size. The nanoprisms have an average base size of 35 nm with 35 nm edges, and the nanowires have a diameter of 10-15 nm; both were obtained in methanol. Crystal and electronic structure calculations were performed using the Vienna ab initio simulation package (VASP) based on density functional theory (DFT). Considering the band gap of pristine CdLa2S4 in the visible region (2.3 eV), we have demonstrated CdLa2S4 as a photocatalyst for the production of H-2 under solar light. Nanostructured CdLa2S4 prisms gave the maximum hydrogen production, i.e. 2552 mu mol h(-1). Being a stable ternary nanostructured metal sulfide (with nanohexagons, nanoprisms, nanowires), CdLa2S4 may have other potential prospective applications in solar cells and optoelectronic devices.

Organization of cubic CeO2 nanoparticles on the edges of self assembled tapered ZnO nanorods via a template free one-pot synthesis: significant cathodoluminescence and field emission properties - Warule, Sambhaji S.; Chaudhari, Nilima S.; Kale, Bharat B.; Patil, Kashinath R.; Koinkar, Pankaj M.; More, Mahendra A.; Murakami, Ri-ichi (Journal of Materials Chemistry, 2012)
The present investigation explores the controlled architecture of a CeO2-ZnO nanocomposite via a template-free, low temperature, facile single step solvothermal approach. This complex architecture depicts cubic single crystalline CeO2 nanoparticles (size similar to 15 nm) grown on the edges of tapered ZnO nanorods with definite orientations and alignments. The formation of wurtzite ZnO, cubic CeO2 and the coexistence of Ce3+ and Ce4+ on the surface of the CeO2-ZnO nanocomposites are confirmed using various characterization tools. The finding of such unique nanostructures by a facile method is exemplified by a plausible growth mechanism. Surprisingly, the aqueous mediated ultrasonication reaction conferred the formation of crystalline ZnO nanotubes of diameter similar to 50 nm. Spatially resolved cathodoluminescence spectra are obtained by linearly scanning an individual CeO2-ZnO nanorod along its length, which reveals the size-dependent surface effects. Interestingly, such hybrid CeO2-ZnO nanoarchitecture is observed to exhibit enhanced field emission properties, demonstrating better current stability as compared to other ZnO nanostructures. This is attributed mainly to strong surface interactions between the Ce-ionic species and the ZnO nanorods. Herein, a soft-chemical approach is used for the first time to architect a binary oxide nanostructure, which is otherwise accomplished using high temperature techniques, as reported elsewhere. Also, the present work not only gives insight into understanding the hierarchical growth behaviour of the CeO2-ZnO nanocomposite in a solution phase synthetic system, but also provides an efficient route to enhance the field emission performance of ZnO nanostructures, which could be extended to other potential applications, such as chemical sensors, optoelectronic devices and photocatalysts.

Enhanced electrochromic coloration in Ag nanoparticle decorated WO3 thin films - Kharade, Rohini R.; Mali, Sawanta S.; Patil, Satish P.; Patil, Kashinath R.; Gang, Myong G.; Patil, Pramod S.; Kim, Jin H.; Bhosale, Popatrao N. (Electrochimica Acta, 2013)
WO3/Ag composite thin films were prepared by microwave assisted sol-gel synthesis (MW-SGS) of WO3 followed by vacuum evaporation of Ag nanoparticles and their enhanced electrochromic coloration was investigated. The composition and morphology of WO3 thin films with different thickness of Ag layer obtained by vacuum evaporation were investigated. Distinct plasmon absorption bands of Ag nanoparticle thin films were obtained. The optical band gap energy of WO3/Ag films decreased with increasing the Ag layer thickness. The surface of these films has been examined using X-ray photoelectron spectroscopy (XPS) to gain information about the chemical states of species present at surfaces. Experimental results indicated that the conductivity of the films increased after surface modification by Ag layer. To investigate the origin of enhanced electrochromic absorption in optical properties, working electrode consisting of WO3/Ag thin film was used and observed the optical properties during electrochemical reaction. It was found that composite electrode shows enhancement in electrochromic properties in terms of optical modulation (Delta OD) and coloration efficiency (eta). (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Ag2WO4; CIE coordinates; Electrochromism; SPR; WO3/Ag composite thin films

Mixed Co-Mn oxide-catalysed selective aerobic oxidation of vanillyl alcohol to vanillin in base-free conditions - Jha, Ajay; Patil, Kashinath R.; Rode, Chandrashekhar V. (Chempluschem, 2013)
Manganese-doped cobalt mixed oxide (MnCo-MO) catalyst was prepared by a solvothermal method. The as-prepared catalyst was characterised by X-ray photoelectron spectroscopy, H-2 temperature-programmed reduction, O-2 temperature-programmed oxidation and XRD. This catalyst gave 62% conversion with 83% selectivity to vanillin in 2hours for the liquid-phase air oxidation of vanillyl alcohol without using base. Three different types of metal oxides were observed in the prepared catalyst, which could be identified as Co3O4, Mn3O4 and CoMn2O4. Among these, the tetragonal phase of CoMn2O4 was found to be more active and selective for vanillyl alcohol oxidation than Co3O4 and Mn3O4. High-resolution TEM characterisation revealed the morphology of MnCo-MO nanorods with a particle size of 10nm. Successful recycling of the catalyst was also established in this oxidation reaction.
Keywords: aerobic oxidation; cobalt; heterogeneous catalysis; manganese; spinel phases

Spin transport and magnetic correlation parameters for graphene-like nanocarbon sheets doped with nitrogen - Alegaonkar, Ashwini P.; Kumar, Arvind; Patil, Sagar H.; Patil, Kashinath R.; Pardeshi, Satish K.; Alegaonkar, Prashant S. (Journal of Physical Chemistry C, 2013)
Globally, graphene magnetism has captivated the attention of researchers in recent years. To obtain magnetic ordering, irregularities in the carbon network, like defects, adatoms, etc., are essential. Herein, we report on spin transport and magnetic correlations in graphene-like nanocarbon sheets (GNCs) that were doped with nitrogen by use of tetrakis(dimethylamino)ethylene (TDAE). The spin transport measurements, performed by electron spin resonance technique, showed that both spin-spin and spin-lattice relaxation times are increased by nitrogen doping. The magnetic correlations, measured on a vibrating sample magnetometer, showed that ordering parameters are reduced for nitrogen-loaded GNCs. Chemical analysis, carried out via electron spectroscopy, revealed that nitrogen atoms exchange couples electron-to-hole with the carbon network Analysis of I-V measurements showed that higher-order resistance is appreciably decreased for nitrogen-doped GNCs. The observed decrease is due to an increase in nonbonding states baying small local density. After doping, states in this region may be localized pi spin populated around the doped region. By and large, the approximately 20% magnetization that exists in GNCs is found to be reduced to 5% by introduction of nitrogen.

Facile room temperature synthesis of ZnO nanoflower thin films grown at a solid-liquid interface - Jadhav, Aarti H.; Patil, Sagar H.; Sathaye, Shivaram D.; Patil, Kashinath R. (Journal of Materials Science, 2014)
Hierarchical ZnO films consisting of nanoflower particulates are successfully grown by a solid-liquid interface reaction technique at room temperature without additives like surfactants, capping agent, or complexing agent. The structural, morphological, and photocatalytic properties of these films are studied using scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), and UV-Vis spectroscopy. The nucleation, growth processes and hence the resulting morphology of the end product can be regulated by changing the concentration of LiOH and the time of reaction. SEM throws light on the chronology of the flower formation by studying the intermediate morphology. Electron microscopy results indicated that these ZnO nanostructures self-assembled to produce flower-like nanostructures. The highest photocatalytic efficiency was observed for the films prepared at the concentration of LiOH 0.5 mg/mL in ethanol at 24 h. On the basis of the results, a plausible growth mechanism for the formation of flower-like ZnO nanostructures is discussed.

Role of iron oxide impurities in electrocatalysis by multiwall carbon nanotubes: An investigation using a novel magnetically modified ITO electrodes - Samant, Kanchan M.; Joshi, Vrushali S.; Patil, Kashinath R.; Haram, Santosh K. (Bulletin of Materials Science, 2014)
The role of iron oxide impurities in the electrocatalytic properties of multiwall carbon nanotubes (MWCNTs) prepared by catalytic chemical vapour decomposition method (CCVD) is studied in detail. A novel magnetically modified electrodes have been developed by which MWCNTs were immobilized on indium-tin oxide (ITO) electrodes, without any chemical binders. The electro-catalytic oxidation of dopamine, and reduction of hydrogen peroxide have been studied by cyclic voltammetry on magnetically modified electrodes with (i) MWCNTs with occluded iron oxide impurities (Fe-MWCNTs), (ii) MWCNTs grown on iron oxide nanoparticle particulate films (Io-MWCNTs) and (iii) pristine iron oxide nanoparticle particulate film (Io-NPs). A shift towards less positive potentials for the oxidation of dopamine was observed which is in the order of Fe-MWCNTs < Io-MWCNTs < Io-NPs. Similarly, trend towards less negative potentials for the reduction of hydrogen peroxide was observed. Thus, the electrocatalytic activities displayed by MWCNTs have been attributed to the iron oxide impurities associated with it. The systematic variation was related to the nature of interaction of iron oxide nanoparticles with MWCNT surface.
Keywords: dopamine; Hydrogen peroxide; iron oxide nanoparticles; magnetically-modified electrode; Multiwall carbon nanotubes (MWCNTs)

Studies on morphology of polyaniline films formed at liquid-liquid and solid-liquid interfaces at 25 and 5 A degrees C, respectively, and effect of doping - Waghmode, Babasaheb J.; Patil, Sagar H.; Jahagirdar, Mandar M.; Patil, Virendra S.; Waichal, Rupali P.; Malkhede, Dipalee D.; Sathaye, Shivaram D.; Patil, Kashinath R. (Colloid and Polymer Science, 2014)
It is well accepted that the morphology of the nanomaterials has great effect on the properties and hence their applications. Therefore, morphology of materials has become a focus of research in the scientific world. The present study shows that interfacial polymerization and subsequent self-assembly provides a control over the morphology, nanorod/nanosheet, of polyaniline (PANI) films synthesized by liquid-liquid interface reaction technique and solid-liquid interface reaction technique. The synthesized PANI films and its particulate structure are characterized by using various spectroscopic techniques such as UV-visible, ATR-IR, Raman and XPS. The study confirmed the formation, the structure, the size and shape of particles and morphology of PANI by using analytical techniques namely, SAED, SEM and TEM. An important observation is that doping with HCl significantly improves the nanorod formation at the interface. The doped PANI electrode exhibits a higher area with rectangular shape in CV cycle and better cycle stability when compared with the performance of undoped PANI films. We believe that the results of these studies can give valuable leads to manoeuvre formation of PANI films with desired morphology for various applications.
Keywords: interfacial polymerization; Liquid-liquid interface; Nanorods; nanosheets; polyaniline; Self-assembly; Solid-liquid interface; Thin films

Vapor-liquid-solid growth of one-dimensional tin sulfide (sns) nanostructures with promising field emission behavior - Suryawanshi, Sachin R.; Warule, Sambhaji S.; Patil, Sandip S.; Patil, Kashinath R.; More, Mahendra A. (ACS Applied Materials & Interfaces, 2014)
Single-crystalline ultralong tin sulfide (SnS) nanowires has been grown by a thermal evaporation technique under optimized conditions on gold-coated silicon substrates, and for the first time, field emission investigations on the SnS nanowires at the base pressure of 1 X 10(-8) mbar are reported. It has been revealed that the surface morphology of the as-synthesized SnS nanostructures is significantly influenced by the deposition temperature and duration. Structural and morphological analyses of as-synthesized SnS nanostructures have been carried out using X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). To understand the optical and electronic properties of as-synthesized SnS nanowires, ultraviolet-visible (UV-vis), photo-luminescence (PL), and X-ray photoelectron spectroscopy (XPS) studies were carried out. The SEM and TEM measurements reveal the formation of ultralong SnS nanowires, with an average diameter of 80 nm. A plausible explanation on the vapor-solid-liquid (VLS) growth mechanism based on the experimental results and reported literature has been presented. Furthermore, the field emission characteristics of the SnS nanowires are found to be superior to the other metal chalcogenide nanostructures. The synthesized SnS nanowire emitter delivers a high current density of similar to 2.5 mA/cm(2) at an applied electric field of similar to 4.55 V/mu m. The emission current stability over a period of 6 h is observed to be good. The observed results demonstrate the potential of the SnS nanowire emitter as an electron source for practical applications in vacuum nano/microelectronic devices.
Keywords: Electron emission; ID nanostructure; SnS nanowires; thermal evaporation; vapor-liquid-solid (VLS) growth

Architecturally designed Pt-MoS2 and Pt-graphene composites for electrocatalytic methanol oxidation - Patit, Sagar H.; Anothumakkool, Bihag; Sathaye, Shivaram D.; Patil, Kashinath R. (Physical Chemistry Chemical Physics, 2015)
Thin films consisting of platinum nanoparticles (Pt NPs) with uniform size and distribution have been successfully prepared at a liquid-liquid interface. Apart from the usual substrates like glass, Si etc. the films were also deposited on the surfaces of MoS2 thin films and graphene nanosheets (GNS) respectively, by using a layer-by-layer (LbL) deposition technique to form Pt-MoS2 and Pt-GNS composites. The loading concentration of Pt NPs on MoS2 and GNS can be adjusted by selecting the number and sequence of the component layers during LbL deposition. The Pt thin films, Pt-MoS2 and Pt-GNS nanocomposite thin films are characterized using transmission electron microscopy (TEM), high resolution transmission electron microscopy (HRTEM), energy dispersive X-ray spectrometry (EDS), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). TEM results of the composites show that Pt NPs with sizes in the range of 1 to 3 nm are uniformly dispersed on the MoS2/GNS surface. The catalytic activities of Pt and Pt-composites for the reaction of methanol oxidation are studied using cyclic voltammetry and chronoamperometry. Electrochemical studies reveal that both the Pt-MoS2 and Pt-GNS nanocomposites show excellent electrocatalytic activity towards methanol oxidation. Pt-MoS2 and Pt-GNS nanocomposite electrodes show excellent stability for reuse of the catalyst. A probable mechanism of catalysis has been discussed. We propose that the similar architecture reported here would be promising for the synthesis of high performance catalysts for fuel cells, gas phase reactions, and other applications such as sensors.

Method to form semiconductor quantum dot (QD) thin films by igniting a flame at air-liquid interface: CdS and WO3 - Jadhav, Aarti H.; Patil, Sagar H.; Sathaye, Shivaram D.; Patil, Kashinath R. (Journal of Colloid and Interface Science, 2015)
We reveal an easy, inexpensive, efficient one step flame synthesis of semiconductor/metal oxide thin films at air-liquid interface, subsequently, transferred on suitable substrate. The method has been illustrated by the formation of CdS and Wo(3) QDs thin films. The features of the present method are (1) Growth of thin films consisting of 0.5-2.0 nm sized Quantum Dots (QDs)/(ultra-small nanoparticles) in a short time, at the air-liquid interface which can be suitably transferred by a well-known Blodgett technique to an appropriate substrate, (2) The method is suitable to apply layer by layer (LbL) technique to increase the film thickness as well as forming various compositions as revealed by AFM measurements. The films are characterized for their structure (SAED), morphology (TEM), optical properties (UV-Vis.) and photoluminescence (PL). Possible mechanism of formation of QDs thin film and effect of capping in case of COS QDs is discussed. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: CdS; Flame synthesis; interface; Quantum Dots (QDs); thin film; WO3

Multifunctional polyaniline-tin oxide (PANI-SnO2) nanocomposite: synthesis, electrochemical, and field emission investigations - Patil, Sandip S.; Harpale, Kashmira V.; Koiry, Shankar P.; Patil, Kashinath R.; Aswal, Dinesh K.; More, Mahendra A. (Journal of Applied Polymer Science, 2015)
Synthesis of PANI-SnO2 nanocomposite has been performed using a simple two step chemical oxidative polymerization route. The structural, morphological and chemical properties of the as-synthesized PANI-SnO2 nanocomposite have been revealed by various characterization techniques such as SEM, TEM, XRD, FTIR, and XPS. Interestingly the as-synthesized PANI-SnO2 nanocomposite exhibits supercapacitance value of 721 F g(-1) with energy density 64 Wh kg(-1), which is noticed to be higher than that of pristine SnO2 and PANI nanostructures. Furthermore, the galvanostatic charge-discharge characteristics revealed pseudocapacitive nature of the PANI-SnO2 nanocomposite. The estimated values of charge transfer resistance and series resistance estimated from the Nyquist plot are found to be lower. Along with the supercapacitive nature, PANI-SnO2 nanocomposite showed promising field emission behavior. The threshold field, required to draw emission current density of 1 A/cm(2), is observed to be 0.90 V/m and emission current density of 1.2 mA/cm(2) has been drawn at applied field of approximate to 2.6 V/m. The emission current stability investigated at preset values of 0.02 and 0.1 mA/cm(2) is observed to be fairly stable over duration of more than 3 h. The enhanced supercapacitance values, as well as, the promising field emission characteristics are attributed to the synergic effect of SnO2 nanoparticles and PANI nanotubes. (c) 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41401.
Keywords: conducting polymers; Electrochemistry; nanostructured polymers; surfaces and interfaces

Reduced graphene oxide composite with oxidizable manganese/cobalt mixed oxide for p-cresol oxidation by using molecular oxygen - Jha, Ajay; Patil, Sagar H.; Solanki, Bhanu P.; Ribeiro, Ana P. C.; Castro, Carlos A. N.; Patil, Kashinath R.; Coronas, Alberto; Rode, Chandrashekhar V. (ChemPlusChem, 2015)
A composite of graphene oxide (GO) with mixed oxide (MnCo) was prepared by using a solvothermal method. During the synthesis, both the reduction of GO and growth of metal oxides took place simultaneously. The as-prepared composite material was highly selective for the liquid-phase oxidation of p-cresol to form p-hydroxybenzaldehyde in 71% yield within 1h. The composite material was characterised by SEM, X-ray photoelectron spectroscopy, high-resolution TEM and cyclic voltammetry (CV). A CV study revealed that the increase in the redox potential of the mixed oxide after being supported on GO, led to its higher activity of the catalyst for the oxidation reaction. The stability of the catalyst under the reaction conditions was studied by its successful reuse in three cycles.
Keywords: cyclic voltammetry; graphene; Oxidation; supported catalysts; transition metals

Shape-selective oriented cerium oxide nanocrystals permit assessment of the effect of the exposed facets on catalytic activity and oxygen storage capacity - Sreeremya, Thadathil S.; Krishnan, Asha; Remani, Kottayilpadi C.; Patil, Kashinath R.; Brougham, Dermot F.; Ghosh, Swapankumar (ACS Applied Materials & Interfaces, 2015)
The catalytic performance of a range of nanocrystalline CeO2 samples, prepared to have different morphologies, was measured using two accepted indicators; oxygen storage and diesel soot combustion. The same powders were characterized hi detail by HR-TEM, XRD, XPS, and Raman methods. The study demonstrates that activity is determined by the relative fraction of the active crystallographic planes, not by the specific surface area of the powders. The physical study is a step toward quantitative evaluation of the relative contribution to activity of the different facets. The synthetic protocol permits fabrication of CeO2 nanostructures with preferentially grown active planes, and therefore has potential in developing catalytic applications and in nanocompositing.
Keywords: ceria; chemical activities; crystal facets; nanocrystals; texture coefficient

Synthesis and characterization of FeTiO3 ceramics - Gambhire, Anil B.; Lande, Machhindra K.; Rathod, Sandip B.; Arbad, Balasaheb R.; Vidhate, Kaluram N.; Gholap, Ramakrishna S.; Patil, Kashinath R. (Arabian Journal of Chemistry, 2016)
Nanocrystalline FeTiO3 ceramics powders were prepared by the sol-gel process combined with a surfactant-assisted template method. The resulting powders were calcined at different temperatures ranging from 150 degrees C to 600 degrees C for 2 h in an air. The results revealed that a pure hexagonal phase of FeTiO3 could be obtained at low temperature, 600 degrees C. The phase evolution of FeTiO3 was investigated by X-ray diffraction patterns (XRD), Fourier-transform infrared spectroscopy (FT-IR), and X-ray photoelectron spectroscopy (XPS). Particle size and morphology was studied by transmission electron microscopy (TEM). (C) 2011 Production and hosting by Elsevier B.V. on behalf of King Saud University.
Keywords: Electron microscopy; hexagonal phase; Nanoparticles; sol-gel process; Ti-O bond

Synthesis and study of calixarene-doped polypyrrole-TiO2/ZnO composites: antimicrobial activity and electrochemical sensors - Waghmode, Babasaheb J.; Husain, Zahid; Joshi, Meenal; Sathaye, Shivaram D.; Patil, Kashinath R.; Malkhede, Dipalee D. (Journal of Polymer Research, 2016)
The present communication describes the synthesis of an electroactive nanocomposite of calixarene- doped polypyrrole ( PPY) containing an oxide of Ti/ Zn. The additive TiO2/ ZnO serves as an oxidizing agent for the polymerization, thus avoiding the use of hazardous organic solvents while calixarene doping stabilizes the polymer. The materials synthesized herein were characterized by UV- visible spectroscopy, FT- IR spectroscopy, scanning electron microscopy ( SEM), transmission electron microscopy ( TEM), energy- dispersive X- ray spectroscopy ( EDX), X- ray photoelectron spectroscopy ( XPS), and cyclic voltammetry ( CV) of synthesized nanocomposites. It was revealed that the resulting calixarene- doped polypyrrole- TiO2/ ZnO nanocomposite has ( 1) long- time stability, ( 2) significant electrochemical activity for sensing formaldehyde, and ( 3) good antimicrobial activity.

In situ grown nickel nanoparticles in a calixarene nanoreactor on a graphene-MoS2 support for efficient water electrolysis - Waghmode, Babasaheb J.; Bhange, Siddheshwar N.; Unni, SreeKuttan M.; Patil, Kashinath R.; Malkhede, Dipalee D. (Sustainable Energy & Fuels, 2017)
Electrochemical production of hydrogen, facilitated in electrolysers, holds great promise for energy storage and solar fuel production. Catalysis of the oxygen evolution reaction (OER) is a bottleneck of this process. However, the sluggish OER kinetics and the utilization of precious metal catalysts are key obstacles in the broad deployment of this energy technology. We report the preparation and use of an inexpensive GrMoS(2)SC(8)Ni nanocomposite material as a highly effective OER catalyst in an alkaline electrolyte. Experimental investigations have shown that improvements can be realized in the catalytic performance of Ni metal if it is a component of the composite material. We propose an explanation for these enhancements based on a hydrogen acceptor concept. This concept comprises the stabilization of an *-OOH intermediate, which effectively lowers the potential needed for breaking bonds on the surface. Herein, an inexpensive immobilized SC8 layer was used as the nanoreactor to synthesize metallic Ni nanoparticles (NPs) through an in situ redox process. The process was applied to form immobilized NPs on flat and curved 2D surfaces. The outstanding OER performance of Ni NPs could be attributed to their large surface area, efficient mass and charge transport, and high structural stability arising from the unique SC8 cage structure, built on the GrMoS(2) substrate. The GrMoS(2)SC(8)Ni nanocomposite shows the highest activity, exhibiting a 214 mV overpotential at 10 mA cm(-2) (equivalent to 10% efficiency of solarto-fuel conversion) and a Tafel slope of 31 mV dec(-1) in 1 M KOH solution. It further demonstrates high stability as there is no apparent OER activity loss (based on a chronoamperometry test) or particle aggregation (based on SEM image observation) after a 10 h anodization test. The facile preparation method and high efficiency and durability enable this electrocatalyst to be a promising candidate for future large-scale applications in water splitting. Thus, this work opens a new avenue toward the development of highly efficient, inexpensive OER catalysts.

Calixarene intercalated NiCo layered double hydroxide for enhanced oxygen evolution catalysis - Waghmode, Babasaheb J.; Gaikwad, Aarti P.; Rode, V, Chandrashekhar; Sathaye, Shivaram D.; Patil, Kashinath R.; Malkhede, Dipalee D. (ACS Sustainable Chemistry & Engineering, 2018)
Water splitting provides a promising, sustainable way to resolve problems arising due to depleting fossil fuels. The success needs development of low-cost and high-performance electrode materials. The oxygen evolution reaction (OER) is a crucial reaction in water splitting. The combined Ni and Co oxide developed nanostructures having a small overpotential and fast kinetics of OER. They have drawn considerable attention, because of their theoretically high efficiency, high abundance, low cost, and environmental benignity in comparison with precious metal oxides, such as RuO2 and IrO2. However, the desired efficiency needs the developments of enhanced specific active area and conductivity. In the present communication, we address these issues. Specifically, exfoliation of layer double hydroxide (LDH) is applied to enhance the active surface area. The study reveals that intercalation by calixarene in NiCo LDH affords a multifunctional interlayer to deliver a large active surface area and fast electron transport toward the carbon nano-onion (CNO) support. It favorably lowers the overpotentials in OER (290 mV) and attains Tafel slope of 31 mV/decade. Enhanced conductivity is achieved using CNO as a support for the calixarene intercalated NiCo LDH. These developments offer a synergistic effect in achieving superior electrocatalytic activity for OER. This work gives insight into designing binder-free electrodes in alkaline media with good stability for advanced OER activity.
Keywords: Calixarene; electrocatalyst; Exfoliation; NiCo LDH; Oxygen Evolution Reaction

Methanol oxidation reaction on Pt based electrocatalysts modified ultramicroelectrode (UME): Novel electrochemical method for monitoring rate of CO adsorption - Joshi, Vrushali S.; Poudyal, Durgasha C.; Satpati, Ashis K.; Patil, Kashinath R.; Haram, Santosh K. (Electrochimica Acta, 2018)
Novel fast scan cyclic voltammetry (FSCV) based method has been developed to study methanol oxidation reaction on Pt nanoparticles (PtNPs) based catalysts. To support the cyclic voltammetry measurements at higher scan rates, micron-sized electrode geometries viz. PtNPs loaded on the single strand of carbon fiber (SSCF) and PtNPs decorated multiwalled carbon nanotubes (MWCNTs), loaded on commercial ultramicroelectrode (UME) have been employed. Deconvolution of the voltammograms obtained during methanol oxidation revealed three major anodic peaks. These peaks have been plausibly attributed to the electron transfer processes viz. methanol oxidation into CO/other intermediates, oxidation of these intermediates into CO2 and adsorption of un-oxidized CO on the catalyst surface. The peaks due to CO adsorption have been elucidated as a function of scan rates. The area under the peak as a function of time has been correlated to the rate of CO adsorption on these catalysts. The average rate of CO adsorption in methanol oxidation at Pt-SSCF and Pt-MWCNTs/UME are estimated to be 1.08 x 10(-8) mol cm(-2) s(-1) and 13.5 x 10(-8) mol cm(-2) s(-1) respectively. This novel method is proposed to generalize to any electrocatalysts of interest. (C) 2018 Published by Elsevier Ltd.

To form layer by layer composite film in view of its application as supercapacitor electrode by exploiting the techniques of thin films formation just around the corner - Patil, Sagar H.; Gaikwad, Aarti P.; Sathaye, Shivaram D.; Patil, Kashinath R. (Electrochimica Acta, 2018)
A method is described to form robust composite supercapacitor electrodes consisting of polyaniline (PANI)-graphene (GNS) and PANI-MoS2 nanosheets wherein composites are formed by Layer by Layer (LbL) deposition. PANI layer consisting of 10-15 nm particle size was formed by LLIRT, while GNS and MoS2 layers were formed by modified LLIRT. A special feature of the development is the architecture which is rarely found in the literature wherein singular components are stacked over each other to form a composite. The architecture is found to show strong synergistic effects suitable for high performance supercapacitor applications. The composites were characterized by using X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), high resolution transmission electron microscopy (HRTEM) etc. The characterization indicates the formation of composites having uniform distribution of PANI nanoparticles over the 2D nanosheets of GNS and MoS2 respectively. The electrochemical performance of the composites was evaluated by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and Galvanostatic Charge Discharge (GCD). The composite layer consisting of PANI-GNS alternate layers, showed an excellent specific capacitance (C-sp) of 549 Fg(-1) while PANI-MoS2 alternate layers and PANI layers showed C-sp to be (413 F g(-1)) and (185 F g(-1)) respectively. It is proposed that C-sp stability of the composites is greatly enhanced by the architecture of composite formation through LbL deposition approach. PANI-GNS showed high stability (95% retention of C-sp), PANI-MoS2 (94% retention of C-sp) as against single component capacitance of PANI (67% retention of C-sp). The results reveal the importance of the architecture of composite formation. The architecture of depositing alternate layers of components to form a composite would have special properties leading to synergistic effect in the applications. The present communication is a proof of this concept. It shows the boost in the charge storage resulting in stable robust supercapacitors formation. We predict similar advantages in other applications such as solar energy conversion, sensors, catalysis, etc. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: GNS; Layer-by-Layer deposition; MoS2 nanosheets; polyaniline; Supercapacitors

Graphene-MnO2 composite supercapacitor material accomplished tactically using liquid-liquid and solid-liquid interface reaction techniques - Patil, Sagar H.; Gaikwad, Aarti P.; Waghmode, Babasaheb J.; Sathaye, Shivaram D.; Patil, Kashinath R. (New Journal of Chemistry, 2020)
A novel methodology is described to grow architectures of 3-dimensional graphene nanosheet (GNS)-manganese oxide (MnO2) composite materials to be used in supercapacitors. The in situ growth of the three-dimensional MnO2 fiber-network over the surface of graphene layers is achieved at the solid-liquid interface. The composite electrode shows good electron and charge transfer, rapid plus reversible faradaic reactions and excellent cyclic ability in electrochemical studies. The electrochemical properties of the as-prepared GNS-MnO2/FTO electrode material were assessed by cyclic voltammetry and galvanostatic charge/discharge tests. The specific capacitance of GNS-MnO2 reaches 683 F g(-1) at a current density of 2.2 A g(-1) and shows excellent cycle stability, retaining 96.9% of its initial capacitance up to 5000 cycles. A coulomb efficiency of about 99% displayed by the GNS-MnO2/FTO electrode is an excellent performance for a desired supercapacitor material. Herein, the charge storage mechanism in 3-dimensional graphene nanosheet (GNS)-manganese oxide (MnO2) composite is discussed in detail. Furthermore, at an elevated current density of similar to 10.86 A g(-1), a power density of similar to 6.235 kW kg(-1) is achieved, maintaining an energy density of similar to 7.99 kW h kg(-1); thus, it demonstrates promising potential as an electrode material for supercapacitor application.